2020
DOI: 10.1007/s10096-020-03812-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of multidrug-resistant Gram-negative pathogens in three tertiary hospitals in Cairo, Egypt

Abstract: High rates of antimicrobial resistance (AMR) among Gram-negative pathogens (GNP) have been reported in Egypt. Antimicrobial surveillance and identifying the genetic basis of AMR provide important information to optimize patient care. In this study, we aimed to identify the beta-lactam resistance phenotypes and genotypes of multidrug-resistant (MDR) non-repetitive GNP from 3 tertiary hospitals in Egypt. WZe studied 495 non-repetitive MDR Gram-negative isolates from patients with complicated intra-abdominal infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
8
16
0
Order By: Relevance
“…Many studies in Egypt and other countries showed that the most commonly detected β-lactamase-encoding gene among the ESBL-producing Enterobacteriaceae was bla CTX-M [55,58] whereas, the bla CTX-M gene was able to be horizontally transferred by several mobile genetic elements [59]. Our data showed that bla CTX-M-15 was the most frequently observed ESBL-encoding gene (found among 89% of E. coli isolates and 86% of K. pneumoniae isolates) and this finding was consistent with the results of other studies performed in Egypt which indicated that bla CTX-M-15 was the most common ESBL encoding gene among ESBL-producing Enterobacteriaceae [55,60,61]. Besides, the next most frequently detected gene was bla TEM-1 which was found in 87% of E. coli isolates and 74% of K. pneumoniae isolates.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Many studies in Egypt and other countries showed that the most commonly detected β-lactamase-encoding gene among the ESBL-producing Enterobacteriaceae was bla CTX-M [55,58] whereas, the bla CTX-M gene was able to be horizontally transferred by several mobile genetic elements [59]. Our data showed that bla CTX-M-15 was the most frequently observed ESBL-encoding gene (found among 89% of E. coli isolates and 86% of K. pneumoniae isolates) and this finding was consistent with the results of other studies performed in Egypt which indicated that bla CTX-M-15 was the most common ESBL encoding gene among ESBL-producing Enterobacteriaceae [55,60,61]. Besides, the next most frequently detected gene was bla TEM-1 which was found in 87% of E. coli isolates and 74% of K. pneumoniae isolates.…”
Section: Discussionsupporting
confidence: 89%
“…Results of various studies on K. pneumoniae in Egypt are coincident with the current study as they reported that the NDM gene was the most predominant detectable carbapenemase gene followed by VIM [32,84]. On the other hand, El kholy et al found that bla OXA-48 dominated (40.6%) followed by bla NDM1 (23.7%) among K. pneumoniae isolates and a small percentage of E. coli harbored bla NDM-1 [61]. It was reported that the NDM1 gene is harbored by diverse plasmids that also carry multiple resistance genes to macrolide, rifampin, carbapenem, cephalosporin, and Sulfamethoxazole and few treatment options are available for those strains which carried this gene [85].…”
Section: Discussionsupporting
confidence: 86%
“…Our study demonstrated that the expression of the AmpC gene was detected in a total of 54 (48.65%) isolates of International Journal of Microbiology P. aeruginosa, K. pneumoniae, and E. faecium with no significant difference in the AmpC expression level concerning the type of infection or the source of specimen, urine (AmpC expression of 50.45% where n � 56), sputum (AmpC expression of 25.23% where n � 28), or wound swab (AmpC expression of 24.32% where n � 27). ese findings are consistent with the results of another study from Egypt regarding the expression of AmpC β-lactamase in microorganisms obtained from Ain Shams University Hospital of Egypt, indicating that 34.8% (22/46) isolates of K. pneumoniae showed overexpression of the AmpC gene [35,36]. We found that 60% of isolates tested in this study were MDR, which is along the same line of another study conducted in Egypt, and found that 87.5% of the clinical isolates were MDR [37].…”
Section: Discussionsupporting
confidence: 91%
“…Rising incidences of Gram negative bacteria (GNB) have become an immense problem worldwide as it may decrease the therapeutic choices considerably and renders anti-bacterial drugs ineffective. In Gram-negative pathogens, resistance has led into a principal cause of morbidity and mortality and a grave public health concern globally, specifically among Enterobacteriaceae family and non-fermenters 1,2 . The expansion of bacterial resistance has grown together with antimicrobial remedy from many years, but merely the GNB have recently begun to exhibit endurance to all regularly employed stages of antimicrobials.…”
Section: Gram-negative Pathogens and Antimicrobial Resistancementioning
confidence: 99%
“…but in addition, it is constantly increasing in Enterobacteriaceae too, especially Klebsiella spp. and is an excellent marker for such situations 1 .…”
Section: Gram-negative Pathogens and Antimicrobial Resistancementioning
confidence: 99%